Impactos econômicos dos jogos Rio 2016 no município e na regi\~ao metropolitana do Rio de Janeiro - Glauter Rocha; Herton Ellery Araújo; Ana Luiza Machado de Codes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This paper aims to apprehend the economic impact of the 2016 Olympic Games, measuring their effects on the gross domestic product (GDP) per capita of both Rio de Janeiro city and its metropolitan area, from 2012 to 2015. By using the synthetic control method, we found out that the games delayed and mitigated the effects of the national intense macroeconomic crisis on the Rio's GDP per capita. The results point out that there were substantial increasing positive effects during those years, for both municipal and metropolitan levels. In the first case, the GDP per capita would have been almost 7.5% smaller if the games hadn't happened-which means it was approximately R 3,694.76/year higher than it would have been in a no games scenario. Regarding the metropolitan area, the GDP per capita would have been nearly 5.1% lesser. It improved about R 1,912.38/year due to the intervention. Furthermore, we verified that, if the games had not taken place, Rio's real GDP per capita would have gone back to 2007 levels. Because of the games, its least level equaled that of 2012.
Keywords: Z20; 330; Olympics; Olympic Games; Rio 2016; sinthetic control method